2013
DOI: 10.3945/jn.112.167098
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Breakfast and the Type of Breakfast Consumed Are Positively Associated with Nutrient Intakes and Adequacy of Canadian Adults

Abstract: Few studies have assessed the associations between breakfast intake and nutrient adequacy [where inadequacy reflects prevalence of usual intakes below the estimated average requirement (EAR) and potential excess reflects the prevalence above the tolerable upper intake level (UL)]. This study examined associations among breakfast, nutrient intakes, and nutrient adequacy in Canadian adults. Respondents aged ≥19 y in the Canadian Community Health Survey 2.2 (n = 19,913) were classified as breakfast nonconsumers (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 16 publications
10
63
1
Order By: Relevance
“…Furthermore, in line with our results micronutrient adequacy tended to be higher in RTEC consumers compared to non-consumers in several of these studies, especially for calcium. [2126] Of note, the lowest level of inadequate intake in the current study was for calcium, with about two thirds of all children failing to meet 80% of the RNI, and this was more prevalent in the older children. The nationwide SEANUTS study also recently highlighted calcium as a nutrient of concern in Malaysian children.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, in line with our results micronutrient adequacy tended to be higher in RTEC consumers compared to non-consumers in several of these studies, especially for calcium. [2126] Of note, the lowest level of inadequate intake in the current study was for calcium, with about two thirds of all children failing to meet 80% of the RNI, and this was more prevalent in the older children. The nationwide SEANUTS study also recently highlighted calcium as a nutrient of concern in Malaysian children.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, fortification practices might have contributed to the discrepancy. In Canada, the addition of 0.31 mg vitamin B 6 per 100 g flour and 0.6 mg per 100 g of breakfast cereal is an optional and yet widespread fortification practice (Barr, DiFrancesco, & Fulgoni, ; Canada Food Inspection Agency, ). In our study cohort, breakfast cereals were the highest ranked fortified food contributing to total vitamin B 6 intake in early pregnancy (Masih et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other countries have also shown that omitting breakfast or having irregular breakfast habits is associated with a less favourable dietary intake, such as lower total daily intakes of various nutrients (26,27) and a low frequency of fruit and vegetable intake (28,29) . Fish and vegetable intakes were particularly low on days when dinner was not consumed.…”
Section: Meal Skippingmentioning
confidence: 99%